Semiotics Analysis of Gojek Advertisements on Instagram - Maulana, Mohammad Irfan (Faculty of Humanities, Universitas Jenderal Soedirman, 2022)
The rapid development of the era has made changes in various aspects of life, including the way of communication. One of the things the company does to communicate its message to its target audience is through advertising on Instagram social media. This article was created to analyze the signifiers and signified in advertisements, especially those published by Gojek on Instagram on 15 and 17 October 2021 using the Ferdinand de Saussure sign approach. This study uses qualitative methods to conduct research in collecting and analyzing data. The study finds 35 signifiers in 3 ads published on 15 October and 13 signigiers in 2 ads published on 17 October. October 2021.